THE IMPACT OF SOCIAL MEDIA INFLUENCERS AGE CUE ON CHARITABLE INTENTIONS FOR DISASTER RELIEF IN INDONESIA - Muhammad Choerul Umam; C. Dyah Sulistyaningrum Indrawati; Dydik Kurniawan; Priyono Tri Febrianto (GeoEco, 2026)
Indonesia’s high disaster vulnerability has elevated the role of social media influencers in mobilizing charitable support, yet the influence of specific cues such as age particularly among older audiences remains underexplored. This study investigates the impact of social media influencers' age cues on charitable intentions for disaster relief in Indonesia, drawing on social comparison theory. Through three sequential experiments involving Indonesian participants aged 55 and older (N = 120, 140, and 160 respectively), the research examines how influencer age cues affect charitable intentions both directly (assimilation) and indirectly through age identity as a mediator. Additionally, the study explores the moderating roles of disaster severity and community involvement, as well as the boundary conditions of intrapersonal and interpersonal constraints. Study 1, a one-factor between-subjects experiment on Instagram, found that older influencers significantly increase charitable intentions among older audiences. Study 2, a 2×2 factorial design on Facebook, demonstrated that this effect is amplified in severe disaster scenarios. Study 3, a 2×2 factorial design on YouTube, revealed that solo relief efforts strengthen the influence of older influencers compared to collective efforts. Across all studies, age identity mediated the relationship between influencer age cues and charitable intentions. These findings provide theoretical contributions to social comparison theory in influencer marketing and practical implications for disaster management organizations seeking to design effective charitable campaigns targeting older demographics.